2019
DOI: 10.1002/slct.201802919
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3/PVP as Green Homogeneous Catalyst to Synthesize 5‐Amino‐1H‐Pyrazole‐4‐Carbonitriles from Malononitrile Derivatives

Abstract: The homogenous catalytic system “FeCl3/PVP” and green solvent system “water/PEG‐400” has been presented as a green pathway to synthesize 4‐amino‐1‐aryl‐1H‐pyrazole‐4‐carbonitrile and its derivatives from a series of phenyl hydrazines and malononitriles. The new approach enhanced the reaction yield of the desired product up to 97% in 2–4 h time whereas the traditional thermal method gives only 87% maximum yield in relatively longer reaction time (3‐7 h). The catalytic system has remarkable benefits such as it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…With 5-aminopyrazoles 14a-d in hand, the authors transformed them into the carboxamide derivatives 15a-d, which then were evaluated against three fungal strains and as inhibitory compounds against succinate dehydrogenase. A year later, Elnagdy and Sarma [30] reported a homogenous catalytic system using FeCl3/PVP and green solvent water/PEG-400 to synthesize 4-amino-1-aryl-1Hpyrazole-4-carbonitriles 17a-q using a cyclocondensation reaction of arylhydrazines 9af with malononitrile derivatives 16a-c. A mixture of FeCl3 and polyvinyl pyrrolidine (PVP) was used to accelerate the addition of 9a-f to the double bond of 16a-c; then, an intramolecular cyclization allows the formation of products 17a-q in up to 97% yield with reaction times of 2-4 h (Scheme 4b). In 2020, Sapkal and Kamble [31] obtained 5-aminopyrazole-4-carbonitriles 20a-m using a green protocol based on a three-component cyclocondensation of phenylhydrazine 9a, aldehyde derivatives 18a-m, and malononitrile (19) adding sodium p-toluenesulfonate (NaPTS) as a catalyst in aqueous media (Scheme 5a).…”
Section: Aminopyrazolesmentioning
confidence: 99%
“…With 5-aminopyrazoles 14a-d in hand, the authors transformed them into the carboxamide derivatives 15a-d, which then were evaluated against three fungal strains and as inhibitory compounds against succinate dehydrogenase. A year later, Elnagdy and Sarma [30] reported a homogenous catalytic system using FeCl3/PVP and green solvent water/PEG-400 to synthesize 4-amino-1-aryl-1Hpyrazole-4-carbonitriles 17a-q using a cyclocondensation reaction of arylhydrazines 9af with malononitrile derivatives 16a-c. A mixture of FeCl3 and polyvinyl pyrrolidine (PVP) was used to accelerate the addition of 9a-f to the double bond of 16a-c; then, an intramolecular cyclization allows the formation of products 17a-q in up to 97% yield with reaction times of 2-4 h (Scheme 4b). In 2020, Sapkal and Kamble [31] obtained 5-aminopyrazole-4-carbonitriles 20a-m using a green protocol based on a three-component cyclocondensation of phenylhydrazine 9a, aldehyde derivatives 18a-m, and malononitrile (19) adding sodium p-toluenesulfonate (NaPTS) as a catalyst in aqueous media (Scheme 5a).…”
Section: Aminopyrazolesmentioning
confidence: 99%
“…The reaction executed by Elnagdy and Sharma in 2019 became successful by using the homogenous catalyst FeCl3-PVP (5 mol % FeCl3) in the water/PEG-400 (2:1) medium for 2-4 h (Scheme 2). 38 Template for SYNTHESIS Thieme Dehghan-Manshadia et al in 2021 have reported the CeO2/CuO@GQDs@NH2 nanocomposite catalyzed reaction of phenylhydrazine, dimethyl acetylenedicarboxylate and arylaldehyde at ambient temperature in water solvent to obtain the bispyrazole derivatives 9 in good yield (82-94%). Initially, the reaction was attempted in the presence of p-TSA, Et3N, CeO2/CuO, CeO2/CuO@GQDs and CeO2/CuO@GQDs@NH2 nanocomposite.…”
Section: Synthesis Of Polyfunctionalized Pyrazolesmentioning
confidence: 99%
“…Elnagdy and Sarma, in 2019, performed the room temperature reaction of different arylhydrazines with malononitrile derivatives using the homogenous catalyst FeCl 3 -PVP (5 mol% FeCl 3 ) in water/PEG-400 (2:1) medium for 2-4 h for the synthesis of several 5-amino-4-cyanopyrazoles in high 89-97% yield (Scheme 2). 38 Scheme 2 FeCl 3 /PVP-catalyzed synthesis of pyrazoles in H 2 O/PEG-400…”
Section: Synthesis Of Polyfunctionalized Pyrazolesmentioning
confidence: 99%
“…The prevalence of pyrazole cores in biologically active molecules causes the sustained interest of chemists to this class of heterocyclic compounds . Pyrazole derivatives are used as agrochemicals, acaricides, fungicides, herbicides, pharmaceuticals, etc .…”
Section: Introductionmentioning
confidence: 99%